2008
DOI: 10.3201/eid1402.070725
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Personal Protective Measures to Prevent Lyme Disease

Abstract: After the manufacture of Lyme vaccine was discontinued in 2002, strategies to prevent Lyme disease (LD) have focused on personal protective measures. Effectiveness of these measures has not been conclusively demonstrated. The aim of our case-control study was to assess the effectiveness of personal preventive measures in a highly disease-endemic area. Case-patients were persons with LD reported to Connecticut's Department of Public Health and classifi ed as having defi nite, possible, or unlikely LD. Agematche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 12 publications
3
72
1
4
Order By: Relevance
“…Similar findings have been reported from the Netherlands [27], the USA [28], Switzerland and Canada [29]. Even when adopted, most personal preventative measures are not highly effective [30][31][32]. Whilst some innovations promise greater risk reduction, especially those relating to acaracide treated clothes [33], basic social barriers to engagement remain.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar findings have been reported from the Netherlands [27], the USA [28], Switzerland and Canada [29]. Even when adopted, most personal preventative measures are not highly effective [30][31][32]. Whilst some innovations promise greater risk reduction, especially those relating to acaracide treated clothes [33], basic social barriers to engagement remain.…”
Section: Introductionsupporting
confidence: 61%
“…Following a case-controlled evaluation, Vázquez et al [32] concluded educational work to encourage personal preventative measures should continue, but given its limited success so far and the unavailability of a vaccine, habitat level interventions to decrease LD hazard should be developed in areas of high tick-human contact. Unfortunately, some suggested tactics may negatively affect ecosystem health.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presented study it was determined that the lowest seropositivity in subjects using repellents was close to the level of significance (P=0.070). Moreover, Vázquez et al [22] demonstrated that the use of tick repellents on the skin or clothing while outdoors was also effective (effectiveness of 20%) in preventing LB. The risk of LB infection also increases due to the lack of preventive measures against tick infestation.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of tick bite prevention recommended by the National Institute for Occupational Safety and Health (NIOSH 2008) for outdoor workers include the following: wearing light-colored protective clothing, tucking pants into socks or boots, regular application of insect repellant to exposed skin, spraying work clothing with permethrin, and daily tick checks. Consistent use of these tick bite prevention methods has been proven effective in preventing tick-borne disease (Vazquez et al 2008), but studies have shown poor adherence to these recommendations (Smith et al 1988). The need for reapplication of insect repellents combined with concerns about the toxicity of the chemicals in the repellents is likely to account for much of the underuse of these preventive measures, indicating that safer and more user-friendly tickbite prevention strategies are needed.…”
Section: Introductionmentioning
confidence: 99%